2018
DOI: 10.1016/j.erss.2018.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Holistic narratives of the renovation experience: Using Q-methodology to improve understanding of domestic energy retrofits in the United Kingdom

Abstract: A B S T R A C TThe energy efficient retrofit of existing building stocks can help to address various social, economic and environmental objectives. As the most cost-effective and least disruptive retrofit options have regularly been implemented as a priority, initiatives that seek to encourage continued retrofit are likely to require thoughtful improvements in their design. Understanding the population of households that may be interested in retrofit as a heterogeneous rather than a homogenous group is a criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 44 publications
0
16
0
1
Order By: Relevance
“…fashionable. A common feature of accounts pointing to the complexity of home energy improvements (Gram-Hanssen, 2014a;Haines & Mitchell, 2014;Kerr et al, 2018;Munro & Leather, 2000;Wilson et al, 2018) mention lifestyle pursuits, aspirations and expectations of home comfort as driving investment and activity. Interesting solutions have emerged from these studies, for instance offering financial assistance for redecoration alongside home energy improvements (Munro & Leather, 2000) or that 'marketing, sales channels and existing points of contact between homeowners and the amenity supply chain [could] be used to target efficiency measures at would-be amenity renovators' (Wilson et al, 2018(Wilson et al, , p. 1342.…”
Section: Energy Retrofit Is Part Of Home Improvementmentioning
confidence: 99%
See 1 more Smart Citation
“…fashionable. A common feature of accounts pointing to the complexity of home energy improvements (Gram-Hanssen, 2014a;Haines & Mitchell, 2014;Kerr et al, 2018;Munro & Leather, 2000;Wilson et al, 2018) mention lifestyle pursuits, aspirations and expectations of home comfort as driving investment and activity. Interesting solutions have emerged from these studies, for instance offering financial assistance for redecoration alongside home energy improvements (Munro & Leather, 2000) or that 'marketing, sales channels and existing points of contact between homeowners and the amenity supply chain [could] be used to target efficiency measures at would-be amenity renovators' (Wilson et al, 2018(Wilson et al, , p. 1342.…”
Section: Energy Retrofit Is Part Of Home Improvementmentioning
confidence: 99%
“…The contradictions between environmental concern and a failure to curtail standards of living (Aro, 2017;Hitchings et al, 2015), including in the context of energy retrofitting homes (Judson & Maller, 2014;Maller & Horne, 2011;Maller et al, 2012), is not new. Indeed, scholars from sociology, anthropology, history, geography and socio-technical studies writing on energy and sustainable consumption have long evidenced that energy use is inherently social, and the materiality of the home co-evolves alongside changing perceptions of basic standards of living, ways of displaying social status, and notions of modernisation (Gram-Hanssen, 2014a;Haines & Mitchell, 2014;Kerr et al, 2018;Munro & Leather, 2000;Wilhite and Lutzenhiser, 1999;Wilson et al, 2018). However, while these studies identify home comfort and homemaking as key considerations in decision making, going further to articulate what these expectations of home comfort are has received little attention in energy debates (Ellsworth-Krebs et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it is widely reported that older homes are far less energy efficient than newer homes [10], and such inefficiencies due to age are likely to cause drafty home environments, hopefully providing the necessary "nudge" for homeowner action [15]. A number of researchers have also focused on the social context surrounding retrofit projects [3,9,16,17] and found that homeowners are more likely to undertake projects if the projects are presented in a context that is socially acceptable to the individual and based on everyday life. This requires a more comprehensive view of homeowners as a heterogenous and diverse group, with varying motivations [16], and of energy retrofits as a regular and routine part of home maintenance and ownership [17].…”
Section: Drivers and Barriers Of Retrofitsmentioning
confidence: 99%
“…On this topic there is ongoing research on a comfort framework that combines aspects of energy efficiency and lifelong living (Kapedani, Herssens, Nuyts, & Verbeeck, 2017;. In a similar vein Kerr, Gouldson, and Barrett (2018) have developed a set of holistic narratives based on the experience of general home renovations as indistinct from energy efficiency.…”
Section: Future Orientation and Comfortmentioning
confidence: 99%